Identification of metallothionein protein in Anodonta woodiana as a biomarker of mercury (Hg) contamination - SATA YOSHIDA SRIE RAHAYU; AZAHRA FADILA; MELTA RINI FAHMI (Nusantara Bioscience, 2023)
Abstract. Rahayu SYS, Fadila A, Fahmi MR. 2023. Identification of metallothionein protein in Anodonta woodiana as a biomarker of mercury (Hg) contamination. Nusantara Bioscience 15: 90-94. Heavy metal contamination can affect the survival of aquatic biota and will accumulate in the bodiesorganisms. Moreover, contamination identification at the molecular level can be analyzed using biomarker analysis. Biomarkers are responses measured individually, ranging from enzymes and xenobiotic measurements to organ and overall conditions. Biomarker analysis can be done by checking the metallothionein protein, this expression can be induced by Reactive Oxygen Species (ROS). Metallothionein (MT) has a thiol group with nucleophilic properties. As a result, this group can make Metallothionein able to find metals and free radicals. Therefore, prevention that can be done to reduce contamination at a higher trophic level requires monitoring the molecular level by observing the metallothionein protein. For example, Anodonta woodiana (Rea, 1834) or kijing taiwan induced by HgCl2 aims to characterize their absorption ability in the environment through metallothionein protein. That was conducted by the SDS-PAGE (Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis) method. SDS-PAGE electrophoresis results showed that the size of the metallothionein protein was 7 kDa, 15 kDa, and >30 kDa. Size >30 kDa is a group of proteins related to stress control or Heat shock protein (Hsp). The presence of Hsp is due to the body increasing stress protein synthesis and metallothionein to reduce normal protein synthesis. Based on the results obtained, this study revealed that A. woodiana could absorb HgCl2, as evidenced by the metallothionein protein characterization results.